Mengelola Citizen Journalist di Media NU Online - Sarjoko Sarjoko (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, State Islamic University Sunan Kalijaga Yogyakarta, 2020)
This research is a qualitative study that discusses how NU Online manages contributors as the backbone of Muslim-based community media in Indonesia. As an alternative media, NU Online has various limitations, including financial limitations so that the media is managed voluntarily. However, NU Online is quite productive, uploading 15-24 posts every day. This study used the interview method to the managing editor and contributors and then analyzed descriptively. The results showed that the implementation of George R. Terry’s management aspects, namely planning, organizing, actuating, and controlling properly, made this media an active and productive community media.Penelitian ini merupakan penelitian kualitatif yang membahas bagaimana NU Online mengelola kontributor sebagai tulang punggung media komunitas berbasis agama Islam di Indonesia. Sebagai sebuah media alternatif, NU Online memiliki berbagai keterbatasan, di antaranya keterbatasan finansial sehingga media tersebut dikelola secara volunteery. Meski demikian NU Online terbilang cukup produktif dengan mengunggah 15-24 tulisan setiap harinya. Penelitian ini menggunakan metode wawancara kepada redaktur pelaksana dan kontributor kemudian dianalisis secara deskirptif. Hasil penelitian menunjukkan bahwa penerapan aspek manajemen George R. Terry, yaitu planning, organizing, actuating, dan controlling dengan baik membuat media ini bisa menjadi media komunitas yang aktif dan produktif.